Development Of Four Species Of Forensic Flies, Estimation Of Post-Mortem Interval And Their Application On Forensic Cases In North Peninsular Malaysia - Krishnan, Kumara Thevan (2011)

(untitled)
The current study explores the relation of the forensic insects and human corpses during the period July 2007 until July 2010 in North Peninsular Malaysia. The larvae were sampled and taken into laboratory, where 50 % of the larvae reared on beef meat ad libitum and the other 50 % killed in warm water (52 ± 10 ºC) and preserved in Kahle’s solution. The species confirmations were done when the reared case maggots emerged. The frequency of occurrence (FO) and dominance (D) of forensic flies were calculated for indoor and outdoor environments. The adults of C. megacephala, C. rufifacies, Liosarcophaga dux and S. nudiseta were maintained as colony and their immature life cycle were established.